2018
DOI: 10.1136/ejhpharm-2018-001679
|View full text |Cite
|
Sign up to set email alerts
|

Perception and practices of public hospital pharmacists towards the antimicrobial stewardship programme in the State of Selangor, Malaysia

Abstract: ObjectiveThe increase in antimicrobial resistance and the lack of new antimicrobial agents in drug discovery pipelines have called for global attention to mitigate the problem of antimicrobial misuse. While an antimicrobial stewardship (AMS) programme has been implemented in Malaysia, the perception and practices of public hospital pharmacists remain unknown. The aim of this study was to determine the perception and practices of Malaysian public hospital pharmacists towards the AMS programme in the state of Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…that the result of this study confirms that South African pharmacists focused their attention on monitoring antimicrobial duration and consumption and participated in AMS ward rounds. The findings of this study strengthen the preceding work confirming the growing involvement and value pharmacists in AMS participation (Kalungia et al 2019;Saleh et al 2020;Tang et al 2020).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…that the result of this study confirms that South African pharmacists focused their attention on monitoring antimicrobial duration and consumption and participated in AMS ward rounds. The findings of this study strengthen the preceding work confirming the growing involvement and value pharmacists in AMS participation (Kalungia et al 2019;Saleh et al 2020;Tang et al 2020).…”
Section: Discussionsupporting
confidence: 89%
“…There was overwhelming evidence that participants identified with the critical role pharmacists play in all facets of AMS. Similarly, a study by Saleh et al (2020) showed that public sector hospital pharmacists agreed that pharmacists have a responsibility to take a prominent role in AMS. These findings are encouraging as positive perceptions of pharmacists reinforce the concept of developing awareness of AMS programmes (Khan et al 2016) and enhance adherence to AMS guidelines (Kalungia et al 2019).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on a margin of error of 7.5%, confidence interval of 95% and response distribution of 50%, the minimum sample size required as calculated using the Raosoft website ( http://www.raosoft.com/samplesize.html ) was 123. Universal sampling was chosen as the response rate of pharmacists was predicted to be between 25 and 40%, based on previous studies utilising similar distribution methods on similar population [ 14 , 15 ]. Response distribution of 50% was chosen as it will yield the most conservative minimum sample size required, as data on proportion of respondents downloading each app were not available.…”
Section: Methodsmentioning
confidence: 99%
“…html) was 123. Universal sampling was chosen as the response rate of pharmacists was predicted to be between 25 and 40%, based on previous studies utilising similar distribution methods on similar population [14,15]. Response distribution of 50% was chosen as it will yield the most conservative minimum sample size required, as data on proportion of respondents downloading each app were not available.…”
Section: Recruitment and Samplingmentioning
confidence: 99%